Faster Acquisition for Dopamine Transporter Imaging Using Swiftscan Step and Shoot Continuous SPECT Without Impairing Visual and Semiquantitative Analysis - Bailly, Matthieu; Le Rouzic, Gilles; Metrard, Gilles; Ribeiro, Maria Joao (Frontiers in Medicine, 2020)
Aim: Dopamine transporter (DAT) imaging with [123I] FP-CIT (DaTSCAN) is an established diagnostic tool in parkinsonism and dementia. Using a Low Energy High Resolution and Sensitivity (LEHRS) collimator and Step & Shoot Continuous scanning mode, Swiftscan Single Photon Emission Computed Tomography (SPECT) (GE Healthcare) enhances sensitivity and enables time or dose reduction. In this phantom and clinical study, we aim to validate a 25% reduction of the acquisition time using Swiftscan and its lack of effect on visual or quantitative analysis. Methods: Anthropomorphic striatal phantom with fillable striata was used. SPECT data from 30 normals (12 men, 18 women; age range 39 – 91 years, mean 71 years +/- 11) and 30 patients with Parkinson disease or other neurodegenerative disease with extra-pyramidal syndrome (16 men, 14 women; age range 43 – 84 years, mean 69 years +/- 10) were also included. Both phantom and clinical data were acquired using Swiftscan and reconstructed with full time and 25%-time reduction. Striatal Binding Ratios (SBR) were calculated using DaTQUANT software. Results: Both in phantom experiments and in clinical cases, visual analysis remained stable and SBR weren’t significantly different whether using Swiftscan or Swiftscan with 25%-time reduction (p<0.001). There was an excellent inter-rater agreement and no-effect of time-reduction on diagnosis nor on image quality. Conclusion: Using Swiftscan step and shoot continuous SPECT mode, 25%-time reduction can be applied to DaTSCAN acquisition protocols, without impairing visual or quantitative analysis.